Acanthemblemaria aceroi, a new species of tube blenny from the Caribbean coast of South America with notes on Acanthemblemaria johnsoni (Teleostei: Chaenopsidae) - Hastings, Philip A.; Eytan, Ron I.; Summers, Adam P. (Zootaxa, 2020)
Acanthemblemaria aceroi new species is described from the upwelling region of the Caribbean coasts of Venezuela and Colombia. It differs from its closest relative, Acanthemblemaria rivasi Stephens, 1970, known from Panama and Costa Rica, in the posterior extent of the infraorbitals, details of head spination, and unique COI sequences. The description of Acanthemblemaria johnsonsi Almany & Baldwin, 1996, heretofore known only from Tobago, is expanded based on specimens from islands offshore of eastern Venezuela.